The Supreme Court reborn : the constitutional revolution in the age of Roosevelt - Leuchtenburg, William E. (William Edward), 1922-2025. (New York : Oxford University Press, 1996)
For almost sixty years, the results of the New Deal have been an accepted part of political life. Social Security, to take one example, is now seen as every American's birthright. But to validate this revolutionary legislation, Franklin Roosevelt had to fight a ferocious battle against the opposition of the Supreme Court--which was entrenched in laissez faire orthodoxy. After many lost battles, Roosevelt won his war with the Court, launching a Constitutional revolution that went far beyond anything he envisioned. In The Supreme Court Reborn, esteemed scholar William E. Leuchtenburg explores th.
Mr. Justice Holmes and three generations of imbeciles -- Mr. Justice Roberts and the railroaders -- The case of the contentious commissioner -- The origins of Franklin D. Roosevelt's "Court-packing" plan -- FDR's "Court-packing" plan -- The case of the Wenatchee chambermaid -- A Klansman joins the court -- The Constitutional Revolution of 1937 -- The birth of America's Second Bill of Rights.
Includes bibliographical references (pages 259-330) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: United States. -- Supreme Court -- History; United States. -- Supreme Court -- Officials and employees -- Selection and appointment -- History; États-Unis. -- Supreme Court -- Histoire; États-Unis. -- Supreme Court -- Fonctionnaires -- Sélection et nomination -- Histoire; United States. -- Supreme Court; États-Unis. -- Supreme Court -- Histoire; Etats-Unis. -- Supreme Court -- 1900-1945.; Etats-Unis. -- Supreme Court -- Fonctionnaires -- Sélection et nomination; Judges -- United States -- History; Constitutional history -- United States; Histoire constitutionnelle -- États-Unis.; Juges -- États-Unis -- Histoire; LAW -- Government -- Federal; Constitutional history; Judges; United States; New Deal; Supreme Court (VS); Justice -- Administration -- États-Unis -- Histoire; Juges -- États-Unis -- Histoire; États-Unis -- Histoire constitutionnelle; Etats-Unis -- Histoire constitutionnelle -- 1900-1945.; History; Electronic books